Design and fabrication of a hydrapulper for disintegrating disused tetra pak® beverage cartons (2015)
This study is aimed at producing paper from disused Tetra Pak® beverage cartons usually found in Nigerian landfills and dumpsites, creating environmental problems. Their use will reduce the overexploitation of trees in the forest for papermaking. A laboratory-scale hydrapulper of 80dm3 was designed and fabricated using locally sourced materials to make the disintegration process cost effective. The performance of the hydrapulper was evaluated at three carton slurry consistencies: low, medium and high consistencies where 3%, 8% and 13% of carton pieces were repulped in water respectively. The fabricated hydrapulper performed satisfactorily to disintegrate and separate the paper component of the cartons from its low density polyethylene and aluminum foil components. The highest average pulp yield of 60.57% was recorded at low consistency although there is no significant difference between the pulp yields at each consistency. It can be concluded that about 80% of the paper component of the carton can be recovered for papermaking.